НОВІТНЯ СТРУКТУРА СИСТЕМИ НАДРОВОГО ПРАВА - Kirin, R.S. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2019)
The article is devoted to the analysis of approaches to determining the place of Law on the Bowels of the Earth in the systems of other branches of Law. The author presents the level structure of the Law on the Bowels of the Earth system based on the principles of differentiating the type of deed with respect to the subsoil (use, protection, safety) for the clan branches and the type of the Bowels of the Earth resource (mineral, geological, underground, geo-energetic), for direct industries. It is proposed to consider Law on the Bowels of the Earth as one of the direct industries of the 1st level in the external structure of the Environmental Law system, and as a general industry of the 2nd level of the internal structure of the system in which the clan branches of the 2nd level are distinguished (Supra-Resource Law, Supra-Defence Law, Subsurface Safety Law) and direct industries of the 2nd level (Mining Law, Geological Law, Underground Law and Geoenergy Law). Schematically, the peculiarity of the formation of the special parts of the patrimonial and direct sectoral elements of the structure of the system of Law on the Bowels of the Earth is that the former are formed by a vertical branch, the latter by a horizontal one. The construction of the newest structure of the system of Law on the Bowels of the Earth is based on the principles of differentiation of the type of activity (use, protection, safety) for generic industries and the type of Bowels of the Earth resource (mineral resources, geological, underground, geo-energy) — for direct industries. The evolution of the research of the features of constructing a sub-legal system shows that the basis for the substantive distinction between Law on the Bowels of the Earth and Mountain Law should be based on the definition of the qualitative homogeneity of their constituent elements. Details of systems of such direct sectoral subsurface elements as Mining and Geological Law are presented. Further scientific research should consolidate the above provisions based on the disclosure of the types, nature and content of both the Bowels of the Earth activities and their objectsubject composition. REFERENCES1. Andreitsev V.I. Ekolohichne pravo: Kurs lektsii: Navch. posibnyk dlia yuryd. fak. vuziv. Kyiv: Venturi, 1996. 208 p. [in Ukrainian].2. Kirin R.S. Kodyfikatsiia zakonodavstva pro nadra: dosvid ta problemy. Dnipro: Nats. hirn. un-t, 2015. 523 p. [in Ukrainian].3. Hetman A.P., Zuiev V.A. Environmental Law: reflections on its origin and prospects for development. Problems of Legality. 2017. Iss. 137. P. 75-91. https://doi.org/10.21564/2414-990x.137.104013 [in Ukrainian].4. Bryhadyr I.V. Shchodo pytannia systemy ekolohichnoho prava. Forum prava. 2015. No. 3. P. 5-10. URL: http://nbuv.gov.ua/UJRN/FP_index.htm_2015_3_3 [in Ukrainian].5. Kostytskyi V.V. Do pytannia pro rozvytok systemy prava ta kryterii yoho podilu na haluzi (na prykladi ekolohichnoho ta povitrianoho prava). URL: http://www.kostytsky.com.ua/upload/doc/sprava.pdf [in Ukrainian].6. Andreitsev V.I. Aktualni problemy hirnychoho prava yak zasobu stymuliuvannia rozvytku hirnychodobuvnoi haluzi. Dop. I-yi Mizhnarod. nauk.-prakt. konf. "Ekoloho-pravovi ta sotsialno-pravovi problemy rozvytku hirnychodobuvnoi haluzi" (m. Dnipropetrovsk, 28-30 travnia 2009 r.). Dnipropetrovsk: Nats. hirn. universytet, 2009. Ch. 1. P. 3-28 [in Ukrainian].7. Makarenko O.Iu. Do pytannia mistsia hirnychoho prava v systemi prava. Dvanadtsiati osinni yurydychni chytannia: zb. tez Mizhnarod. nauk.-prakt. konf. (m. Khmelnytskyi, 8-9 lystopada 2013 r.). U 4 ch. Khmelnytskyi: Khmeln. universytet upravl. i prava, 2013. P. 141-143 [in Ukrainian].8. Makarenko O.Iu. Do pytannia mistsia hirnychoho prava v systemi prava. Advokat. 2013. No. 8. P. 22-26 [in Ukrai nian].9. Eljubaev Zh.S. Teoreticheskie i metodologicheskie problemy pravovogo regulirovanija nedropol’zovanija: otechestvennyj opyt i zarubezhnaja praktika: avtoref. dis. ... d-ra jurid. nauk: 12.00.06. Pavlograd. gos. un-t im. S. Torajgyrova. Almaty, 2010. 43 p. [in Russian].10. Dudikov M.V. Mesto gornogo prava v sisteme otraslej prava. Lex Russica. 2017. No. 8. P. 43-60. https://doi.org/10.17803/1729-5920.2017.129.8.043-060 [in Russian].11. Mel’gunov V.D. Teoreticheskie osnovy gornogo prava Rossii. Ros. gos. un-t nefti i gaza im. I.M. Gubkina. Moskva: Prospekt, 2018. 326 p. [in Russian].12. Kirin R. Statutory and regulatory requirements in the process of mineral mining in Ukraine. Review and analysis. Mining of Mineral Deposits. 2019. No. 13 (2). P. 59-65. https://doi.org/10.33271/mining13.02.059